The influences of age on olfaction: a review - Doty, Richard L.; Kamath, Vidyulata (Frontiers in Psychology, 2014)
Decreased olfactory function is very common in the older population, being present in over half of those between the ages of 65 and 80 years and in over three quarters of those over the age of 80 years. Such dysfunction significantly influences physical well-being and quality of life, nutrition, the enjoyment of food, as well as everyday safety. Indeed a disproportionate number of the elderly die in accident gas poisonings each year. As described in this review, multiple factors contribute to such age-related loss, including altered nasal engorgement, increased propensity for nasal disease, cumulative damage to the olfactory epithelium from viral and other environmental insults, decrements in mucosal metabolizing enzymes, ossification of cribriform plate foramina, loss of selectivity of receptor cells to odorants, changes in neurotransmitter and neuromodulator systems, and neuronal expression of aberrant proteins associated with neurodegenerative disease. It is now well established that decreased smell loss can be an early sign of such neurodegenerative diseases as Alzheimer’s disease and idiopathic Parkinson’s disease. In this review we provide an overview of the anatomy and physiology of the aging olfactory system, how this system is clinically evaluated, and the multiple pathophysiological factors that are associated with its dysfunction.